Management Innovation and Adoption of Emerging Technologies: The Case of Cloud Computing. Issue 1 (19th March 2013) - Khanagha, Saeed; Volberda, Henk; Sidhu, Jatinder; Oshri, Ilan
Abstract : This paper examines the effect of management innovation on a firm's ability to effectively adopt an emerging core technology. Organizing for technological change is often associated with structural dilemmas for incumbents: while structural contingent solutions such as spatially separated units and parallel organizations have been frequently discussed as enablers of handling contradictory requirements of existing and emerging technologies, there is empirical evidence that such solutions are likely to be either unfeasible or unsustainable in the cases of core technologies. Our analysis on the adoption process of a new core technology by a large telecommunication firm reveals the role of management innovation in fulfilling seemingly paradoxical structural requirements of knowledge accumulation in a dynamic knowledge environment. We discuss how a novel structural approach enabled the organization to overcome rigidities in the existing routines and foster a favorable environment for adoption of cloud technology and to overcome organizational challenges, with which the firm's conventional practices failed to commensurate.